Preparation of Nickel Modified Carbon Fibre Electrodes and their Application for Methanol Oxidation - Risbud, Mandar; Baxter, S.; Skyllas-Kazacos, M. (Bentham Open, 2012)
Nickel modified carbon fibre electrodes were prepared by electrochemical oxidation and partial reduction of a graphite fibre electrode with a slow linear potential sweep in 97% H2SO4 solution followed by impregnation & ion exchange with Ni +2 species. The cyclic voltammetry of the modified electrode in an alkaline medium showed electrocatalytic activity towards methanol oxidation which is consistent with the behaviour of a polycrystalline nickel electrode in the same media. The electrode fabricated through the ion exchange with 0.1 M Ni solution provided the most significant response for solutions with lower methanol concentrations up to 0.5 M methanol while at higher concentrations of methanol, a poisoning effect was observed resulting in lower performance